2022
DOI: 10.1186/s40359-021-00710-7
|View full text |Cite
|
Sign up to set email alerts
|

Testing times: the association of intolerance of uncertainty and metacognitive beliefs to test anxiety in college students

Abstract: Background Test anxiety has a detrimental effect on test performance but current interventions for test anxiety have limited efficacy. Therefore, examination of newer psychological models of test anxiety is now required. Two transdiagnostic psychological models of emotional disorders that can account for anxiety are the intolerance of uncertainty model (IUM) and the Self-Regulatory Executive Function (S-REF) model. Intolerance of uncertainty, the stable disposition to find uncertainty distressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
1
3
0
2
Order By: Relevance
“…In addition, there are different studies showing that girls experience more test anxiety than boys (Huntley, Young, Tudur Smith, Jha, & Fisher, 2022;Dowker & Sheridan, 2022). Gender differences in test anxiety may have two separate explanations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are different studies showing that girls experience more test anxiety than boys (Huntley, Young, Tudur Smith, Jha, & Fisher, 2022;Dowker & Sheridan, 2022). Gender differences in test anxiety may have two separate explanations.…”
Section: Discussionmentioning
confidence: 99%
“…When faced with uncertain situations, high IU individuals may engage in risky cognitive explanations and experience increased worry and anxiety, which can contribute to heightened test anxiety among students [17,28,29]. And previous studies have demonstrated that intolerance of uncertainty is a direct predictor of test anxiety [30,31]. Studies have shown that student athletes' intolerance of uncertainty is a significant predictor of test anxiety [32].…”
Section: The Mediating Role Of Intolerance Of Uncertaintymentioning
confidence: 99%
“…Dito isto, deve-se ter em conta que pesquisas prévias evidenciam que outras variáveis que podem contribuir para a ansiedade cognitiva de provas, como, por exemplo, as crenças metacognitivas, a intolerância à incerteza, os pensamentos negativos persistentes (Huntley et al, 2022). Outro aspecto que apresenta relevância na literatura são as estratégias de enfrentamento, nesse sentido, o tipo de estratégia utilizada pode influenciar nos níveis de ansiedade de prova, enfatizando-se o papel das estratégias adaptativas, que se pautam na orientação para a tarefa e na busca de apoio social (Arana & Furlan, 2016;Shimave et al, 2020).…”
Section: Limitações E Orientações Futurasunclassified